Flowering Event of Johannesteijsmannia lanceolata; An Understorey Palm in the Angsi Forest Reserve, Malaysia. - M.Z, Rozainah; U.R, Sinniah (Malaysian Journal of Science, 2006)
The flowering event of an understorey palm; Johannesteijsmannia lanceolata J. Dransfield was investigated in the Angsi Forest Reserve, Malaysia for a total period of 18 months. The study commenced from the appearance of the inflorescence until the fall of mature ripe fruits. Results showed that the flowering phase lasted between 8.7 to 9.4 months and of the 1086 - 2150 fruit sets produced per inflorescence, only 5 - 8 fruits (of 3.5 - 5.0 cm diameter) reached maturity. 71% of the 24 adult trees produced new inflorescences within the study period, with 1.4 inflorescences per plant per year which gives 7 - 11 fruits per plant per year.